An Advanced Study on the Creation of Neutron Stars and Black Stars and How the Chandrasekhar Limit Prevents the Creation of Intermediate Black Stars - P. David Clark (New Insights into Physical Science Vol. 12, 2021)
Using a program written in Excel it was found that a supernova remnant, with a mass between 1.44 and 2.2 solar masses, contracts down to a neutron star. During the collapse the decreasing gravitational potential slows time. Here the pressure becomes high enough to stop the contraction. At greater than 2.2 solar masses, while the remnant is still contracting, the gravitational potential causes time to relatively freeze at the center, and stop the contraction before the pressure gets high enough to stop it, as it did in a neutron star. This also freezes the flow of information concerning the decrease in gravitational potential, thus; the frozen portions remain frozen and do not contract down any further and become imaginary. On top of this frozen center, additional matter physically and relatively contracts and the radius of the freeze point moves out. If the freeze made its way to the surface, it would meet the condition of a black hole, having a Schwarzschild radius; but, it does not quite get there. The surface is not quite frozen. Even though these “almost black holes” do not have an event horizon, they are almost as small as that described by the Schwarzschild radius and due to the gravitational red shift, are very hard to see. A black star has been created. When a white dwarf with a mass greater than the Chandrasekhar limit of 1.44 solar masses contracts, the high pressure and gravity compresses the inner core to a density exceeding 1x109 kg/m3. After it cools and then collapses into a neutron star, it will have a minimum density of 3.5 x 1015 kg/m3 near the surface. This article explains how these two densities relate to why there are no supernova created stellar black stars above 15 solar masses, and why supermassive black stars start at 50,000 solar masses? Extracting limits like these cannot be accomplished using the standard black hole model, but this black star model has revealed these size limits and a lot more. It was found with this model that there is a gap of missing black stars between the largest SBS and the smallest SMBS. This relates to the density gap of unstable matter as pressure compresses it from degenerate white dwarf matter to neutron matter.